Epigenetic Basis of Morphological Variation and Phenotypic Plasticity in Arabidopsis thaliana. Issue 2 (10th February 2015) - Kooke, Rik; Johannes, Frank; Wardenaar, René; Becker, Frank; Etcheverry, Mathilde; Colot, Vincent; Vreugdenhil, Dick; Keurentjes, Joost J.B.
Abstract : Differences in epigenetic marks can explain substantial levels of variation in plant performance and often exert pleiotropic effects. Abstract: Epigenetics is receiving growing attention in the plant science community. Epigenetic modifications are thought to play a particularly important role in fluctuating environments. It is hypothesized that epigenetics contributes to plant phenotypic plasticity because epigenetic modifications, in contrast to DNA sequence variation, are more likely to be reversible. The population of decrease in DNA methylation 1-2 ( ddm1-2 )-derived epigenetic recombinant inbred lines (epiRILs ) in Arabidopsis thaliana is well suited for studying this hypothesis, as DNA methylation differences are maximized and DNA sequence variation is minimized. Here, we report on the extensive heritable epigenetic variation in plant growth and morphology in neutral and saline conditions detected among the epiRILs . Plant performance, in terms of branching and leaf area, was both reduced and enhanced by different quantitative trait loci (QTLs ) in the ddm1-2 inherited epigenotypes. The variation in plasticity associated significantly with certain genomic regions in which the ddm1-2 inherited epigenotypes caused an increased sensitivity to environmental changes, probably due to impaired genetic regulation in the epiRILs . Many of the QTLs for morphology and plasticity overlapped, suggesting major pleiotropic effects. These findings indicate that epigenetics contributes substantially to variation in plant growth, morphology, and plasticity, especially under stress conditions.